2021
DOI: 10.25259/sni_802_2020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cranioplasty timing on the functional neurological outcome and postoperative complications

Abstract: Background: The optimal timing for performing cranioplasty and its effect on functional outcome remains debatable. Multiple confounding factors may come into role; including the material used, surgical technique, cognitive assessment tools, and the overall complications. The aim of this study is to assess the neurological outcome and postoperative complications in patients who underwent early versus late cranioplasty. Methods: A retrospective cohort study was conducted to investigate the neurological outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
1
4
0
2
Order By: Relevance
“…Persistent infection and failures of the reconstruction in extensive procedures represent the main concerns. In this regard, an extended peri-operative antibiotic regimen, lasting up to 6--12 weeks [40 ▪ ,43] is generally advised, although the optimal timing and material for cranioplasty in case of anterior frontal table deformity is still a matter of debate [44 ▪ ,45].…”
Section: Discussionmentioning
confidence: 99%
“…Persistent infection and failures of the reconstruction in extensive procedures represent the main concerns. In this regard, an extended peri-operative antibiotic regimen, lasting up to 6--12 weeks [40 ▪ ,43] is generally advised, although the optimal timing and material for cranioplasty in case of anterior frontal table deformity is still a matter of debate [44 ▪ ,45].…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Similarly, Aloraidi et al reported in their study insignificant differences in the rates of complications after early and late cranioplasty. 37 Hydrocephalus had been reported post cranioplasty in several studies and occurs due to disturbances in the CSF dynamics. 30,35 In our study the risk of occurrence of postoperative hydrocephalus requiring CSF diversion procedure did not differ significantly between early and late groups.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate timing of cranioplasty after craniectomy is also a highly debated subject. While many reports indicate there is no significant difference in cognitive outcomes between cranioplasties performed within 3 months of craniectomy and after, other complications such as hydrocephalus and wound breakdown contribute to outcomes data and may be more significantly impacted by timing [16-18]. Though our data indicate that shorter time to cranioplasty is a predictive factor for the complications studied, this result is confounded by the inclusion of implants placed on day zero of surgery, such as cranioplasty placed after removal of a skull tumor, many of which consisted of repair of secondary skull defects after previous cranioplasty or craniofacial surgery.…”
Section: Discussionmentioning
confidence: 99%